2016
DOI: 10.1038/ejcn.2016.77
|View full text |Cite
|
Sign up to set email alerts
|

Korean traditional Chungkookjang improves body composition, lipid profiles and atherogenic indices in overweight/obese subjects: a double-blind, randomized, crossover, placebo-controlled clinical trial

Abstract: In conclusion, these results suggest that supplementation with Chungkookjang may improve body composition and risk factors for cardiovascular disease in overweight and obese adults.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
36
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(39 citation statements)
references
References 41 publications
1
36
2
Order By: Relevance
“…In the present research, however, the nuclear magnetic resonance revealed the absence of discrepancies in body composition after FFP supplementation. It differs from previous results on fermented food in controlled intervention studies [18,97] and animals models [98] which evidenced a significant decrease in body weight and fat depots. Nevertheless, the absence of significant changes in body composition did not abstain from improvements in glucose homeostasis, what matches well with previous findings in murine models of obesity [99,100].…”
Section: Discussioncontrasting
confidence: 99%
“…In the present research, however, the nuclear magnetic resonance revealed the absence of discrepancies in body composition after FFP supplementation. It differs from previous results on fermented food in controlled intervention studies [18,97] and animals models [98] which evidenced a significant decrease in body weight and fat depots. Nevertheless, the absence of significant changes in body composition did not abstain from improvements in glucose homeostasis, what matches well with previous findings in murine models of obesity [99,100].…”
Section: Discussioncontrasting
confidence: 99%
“…The chungkookjang has also alleviated diabetic symptoms in partial pancreatectomized rats, a type 2 diabetic animal model [ 7 , 10 ] and it has also reduced memory deficit in amyloid-β infused rats, an AD animal model [ 6 ]. Furthermore, 12-week treatment of chungkookjang extract has reported to reduce body fat and waist circumferences and increase lean body mass in overweight/obese women and it has improved lipid profiles in all obese subjects in a double-blinded, randomized, crossover, placebo-controlled clinical trial [ 26 ]. Thus, the results of in vitro studies can be applied to animal and human studies.…”
Section: Discussionmentioning
confidence: 99%
“…At the end of the intervention, it was found that soy isoflavone supplementation significantly reduced metabolic parameters and systolic BP ( P < 0.01), thereby significantly improving cardiovascular risk markers and calculated cardiovascular risk during early menopause compared to soy protein without isoflavones (103). Byun et al (105) described the effect of Chungkookjang supplementation, a Korean fermented soybean food with approximately 50 mg/g of isoflavones, on body composition, dyslipemia, and risk factors for atherosclerosis in overweight/obese subjects. After the intervention, apolipoprotein A1 (Apo A1) was significantly increased in the male Chungkookjang group ( P < 0.05) alone.…”
Section: Flavonoidsmentioning
confidence: 99%
“…Apo A1 was also significantly increased in both the placebo and the Chungkookjang group, whereas apolipoprotein B (Apo B) was significantly decreased in the Chungkookjang group ( P < 0.05). In addition, in the Chungkookjang group, hs-CRP showed a tendency to decreasing and significantly differed between the two groups ( P < 0.05) (105). These results suggest that supplementation with Chungkookjang may improve body composition and risk factors for CVD in overweight and obese adults.…”
Section: Flavonoidsmentioning
confidence: 99%